Agronomic potential of blueberry cultivars in an organic cropping system in the Brazilian subtropics - Chiomento, José Luís Trevizan; Bittencourt, Tobias Furtado; Tortelli, Brenda; Trentin, Thomas dos Santos; Silveira, Diógenes Cecchin; Nienow, Alexandre Augusto (Scientia Agraria Paranaensis, 2022)
The lack of information on the agronomic potential of blueberry cultivars in response to edaphoclimatic and biogeographical characteristics limits the establishment of commercial orchards in the producing regions of southern Brazil. Thus, the research objective was to investigate whether the agronomic potential differs among blueberry cultivars in an organic cultivation system in the Brazilian subtropics. The experiment was conducted in the municipality of Lagoa Vermelha, Brazil, from August 2021 to January 2022, in a commercial orchard. The treatments were three blueberry cultivars belonging to the rabbiteye group (‘Bluegem’, ‘Clímax’ and ‘Florida’), arranged in a completely randomized design, with eight replications. Fruit production and quality were evaluated. ‘Florida’ produced the highest number of fruits and had the highest blueberry production and yield. ‘Bluegem’ and ‘Clímax’ stood out in terms of fruiting rate. ‘Bluegem’ and ‘Florida’ had fruits with greater longitudinal diameter. ‘Clímax’ stood out for its larger cross-sectional fruit diameter and for producing blueberries with higher sugar content, lower citric acid content and better palatability. In conclusion, the three blueberry cultivars in organic cultivation system in the Brazilian subtropics differ in terms of their productive potential and fruit quality. ‘Florida’ has the best yield potential and ‘Clímax’ produces blueberries with the best chemical quality.